Frequency of Infant Colic: Cohort Study - A. Eldesouky, Manar; A. Sharaf, Eman; Mohamed Elbahnacy, Samir; Abdelrashid, Sarah (Journal of Neonatal Surgery, 2025)
Background: Infantile colic (IC) is a common Functional Gastrointestinal Disorder (FGID) affecting infants, characterized by excessive crying and discomfort without an identifiable organic cause. It is hypothesized that gut microbiota imbalance (dysbiosis) plays a crucial role in its etiology. Various risk factors such as delivery method, type of feeding, maternal smoking, and antibiotic exposure may contribute to its occurrence. Objective: our investigation aimed to estimate the frequency of infantile colic and investigate its association with potential risk factors linked to dysbiosis. Methods: This was a cohort study involving 150 newborns admitted to October 6 University Hospital. Based on how they were delivered, infants were split into two distinct groups.: Group 1 (n=92) born via normal vaginal delivery (NVD) and Group 2 (n=58) born via cesarean section (CS). Data collection included demographic characteristics, maternal and neonatal risk factors, type of feeding, and colic frequency. Results: Infantile colic was observed in 46.7% and 44.8% in the NVD and CS groups respectively, exhibiting no significant distinctions between the two delivery methods (p>0.05). Breastfeeding was negatively associated with increased risk of infantile colic, whereas formula and mixed feeding were linked to a higher prevalence (p<0.001). Maternal antibiotic use before delivery and maternal smoking were substantially associated with higher likelihood of colic (p=0.044 and p=0.035, respectively). Neonatal hospitalization also tended to be higher in colicky infants with no statistical significance. Conclusion: The study suggests that infantile colic is prevalent among newborns regardless of the mode of delivery. However, factors including antibiotic use by mothers, smoking, and feeding type play a critical role in its development. Promoting exclusive breastfeeding and minimizing perinatal experiencing antibiotic in the perinatal period may help reduce the incidence of infantile colic.